Pathophysiology of androgen-associated endothelial cell dysfunction in phenotype A polycystic ovarian syndrome revealed by iPSCs modeling - Wu, Chia-Eng; Huang, Chu-Chun; Hsiao, Yung-Jen; Hsu, Chia-Lang; Chen, Tzu-Hsin; Chen, Mei-Jou; Ho, Hong-Nerng (Frontiers in Endocrinology, 2026)
IntroductionAbundant evidence suggests that women with polycystic ovary syndrome (PCOS) have increased metabolic aberrations and cardiovascular risks and present with signs of endothelial cell (EC) dysfunction. However, whether and how androgen is involved in the pathogenesis of EC dysfunction in PCOS remains unclear.MethodsIn this study, induced pluripotent stem cells (iPSCs) were established from three phenotype A PCOS patients (presenting with oligomenorrhea, hyperandrogenism (HA), and polycystic ovarian morphology (PCOM)) and three control participants. These iPSCs were differentiated into ECs (iPSC-derived ECs) using a chemically defined monoculture protocol. To investigate the direct impact of androgen signaling while excluding confounding effects from aromatization into estrogen, dihydrotestosterone (DHT), a potent, non-aromatizable androgen, was used to treat the iPSC-derived ECs from all subjects (three control and three PCOS iPSC-EC lines). Statistical analyses were performed using t-test and one-way or two-way ANOVA followed by appropriate post-hoc tests (p < 0.05).ResultsSingle-cell transcriptomic analysis revealed intrinsic differences in cell cycle process, vascular endothelial growth factor (VEGF) signaling, apoptosis, and androgen signaling in PCOS iPSC-derived ECs. Decreased expression of cell proliferation- and cell cycle-related genes was noted in the PCOS iPSC-derived ECs. Functionally, DHT treatment significantly enhanced cell proliferation and angiogenesis in control iPSC-derived ECs in a dose-dependent manner, as demonstrated by increased tube formation and accelerated wound healing. In contrast, these stimulatory effects were blunted in PCOS iPSC-ECs, particularly at physiological concentrations. These functional impairments were associated with the dysregulation of the androgen receptor (AR)/cyclin-dependent kinase 1 (CDK1)/VEGF signaling pathway.DiscussionIn conclusion, disease-specific iPSCs were successfully generated from phenotype A PCOS patients, providing a robust platform for disease modeling in this distinct subgroup. PCOS iPSC-derived ECs exhibited significantly impaired intrinsic and androgen-induced cell proliferation and angiogenesis. These findings offer novel mechanistic insights into endothelial dysfunction in PCOS and suggest potential implications for increased cardiovascular risk in affected individuals.